Analysis of Gamma-Radiation Background Changes During Periods of Atmospheric Precipitation; Atomic Energy; Vol. 131, iss. 1 - Yakovleva V. S. Valentina Stanislavovna; Poberezhnikov A. D. Andrey Dmitrievich; Yakovlev G. A. Grigory Alekseevich; Kobzev A. A. Aleksey Anatoljevich; Smirnov S. V. Sergey Vasiljevich; Arshinov M. Yu. Mikhail Yurjevich (2021, 2021)
Title screen